Looking for new water-fountain stars. Issue Volume 14:Issue S343(2019) (August 2018) - Uscanga, L.; Gómez, J. F.; Yung, B. H. K.; Imai, H.; Rizzo, J. R.; Suárez, O.; Miranda, L. F.; Trinidad, M. A.; Anglada, G.; Torrelles, J. M.
Abstract: We carried out simultaneous observations of H2 O and OH masers, and radio continuum at 1.3 cm with the Karl G. Jansky Very Large Array (VLA) towards 4 water-fountain candidates. Water fountains (WFs) are evolved stars, in the AGB and post-AGB phase, with collimated jets traced by high-velocity H2 O masers. Up to now, only 15 sources have been confirmed as WFs through interferometric observations. We are interested in the discovery and study of new WFs. A higher number of these sources is important to understand their properties as a group, because they may represent one of the first manifestations of collimated mass-loss in evolved stars. These observations will provide information about the role of magnetic fields in the launching of jets in WFs. Our aim is to ascertain the WF nature of these candidates, and investigate the spatial distribution of the H2 O and OH masers.